Forty years of advertising research on health issues: past learnings and future perspectives. Issue 1 (2nd January 2023) - Koinig, Isabell; Diegelmann, Svenja; Bidmon, Sonja
Abstract: Over the past 40 years, the IJA has addressed various societal and policy issues, amongst them health. In our contribution, we report a systematic review of how advertising in the health context has developed over the past 40 years and how research can be moved forward. For our review, we analyzed articles published in the three leading advertising journals: Journal of Advertising, International Journal of Advertising, and Journal of Advertising Research, concerning their key findings and future research directions. Our systematic review was conducted in correspondence with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement and the method adopted by Bergkvist and Langner (2019). Thus, we searched for articles published in the Journal of Advertising, International Journal of Advertising, and Journal of Advertising Research between 1981 and 2021. We used a keyword search to identify articles containing the word 'health' in the abstract and/or the title. A total of 83 articles were included in this review. For the synthesis of the key findings, we generated four thematic clusters which are (1) nutrition and food advertising, (2) direct-to-consumer and non-prescription drug advertising, (3) smoking prevention, and (4) trends in health advertising. With this paper, we deliver eight avenues of future research that may inspire and propel future research.